SHARPENING THE ENTREPRENEURIAL SPIRIT THROUGH A CHEERFUL BAZAAR FOR 5-6 YEAR OLDS AT TK UNGGULAN ANNUR - Salsabila, Fatmala; Akhtim Wahyuni (Academic Journal Research, 2024)
Objective: This study examines the effectiveness of the Ceria Bazaar, an initiative under the Pancasila Student Profile Strengthening Project (P5), in fostering entrepreneurial spirit among early childhood students at TK Unggulan Annur. The objective is to explore how project-based learning activities can develop creativity, independence, and social responsibility in children. Methods: A descriptive qualitative approach was employed, involving observations, interviews, and documentation to capture the experiences of children, teachers, and parents. Data were analyzed systematically to understand how the Ceria Bazaar contributes to entrepreneurial learning through planning, product creation, and interaction with customers. Results: The findings reveal that the Ceria Bazaar promotes essential entrepreneurial skills such as merchandise management, marketing strategies, and customer interaction. Children gained practical experience in decision-making, financial management, and problem-solving. This activity also enhanced children's self-confidence, teamwork, and creativity while engaging parents and the community in the learning process. Novelty: This study highlights the innovative integration of entrepreneurial education into early childhood learning through a culturally relevant and engaging approach. By combining art-based projects with business concepts, the Ceria Bazaar serves as a replicable model for developing life skills in young learners while reinforcing Pancasila values.